2011
DOI: 10.1002/anie.201101726
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences between the “Relativistic” Triad Gold, Platinum, and Mercury in Catalysis

Abstract: Relativistic effects in the valence shell of the elements reach a maximum in the triad Pt-Au-Hg and determine their catalytic activity in organic reactions. In this Review we examine the catalytic activity of Pt, Au, and Hg compounds for some representative reactions, and discuss the respective benefits and disadvantages along with other relevant properties, such as toxicity, price, and availability. For the reactions considered, gold catalysts are generally more active than mercury or platinum catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
114
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 193 publications
(120 citation statements)
references
References 144 publications
(142 reference statements)
0
114
0
6
Order By: Relevance
“…[1][2][3] Different solid-supported and homogeneous gold catalysts have been reported, and although the latter allows a fine tuning of the electronic/steric properties of the metal through ligand interactions, the former is preferred by economical, practical, and environmental reasons. [4][5][6][7] The electronic nature of gold nanoparticles as a function of size, shape, and interaction with the support has been studied for particular reactions and some structure-activity relationships (SARs) have been made 8-10 though a complete switch of reactivity for a single molecule by fine-tuning the catalytic activity of the nanoparticle is rarely presented.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Different solid-supported and homogeneous gold catalysts have been reported, and although the latter allows a fine tuning of the electronic/steric properties of the metal through ligand interactions, the former is preferred by economical, practical, and environmental reasons. [4][5][6][7] The electronic nature of gold nanoparticles as a function of size, shape, and interaction with the support has been studied for particular reactions and some structure-activity relationships (SARs) have been made 8-10 though a complete switch of reactivity for a single molecule by fine-tuning the catalytic activity of the nanoparticle is rarely presented.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the methanol carbonylation on TiO 2 -supported gold occurs by a route that is analogous to those occurring on other supported metal catalysts. Analogies between the chemistry of gold catalysts and other metals have been proposed for other reactions[71,72]. For example, the group of Corma[71] reported that CeO 2 -supported gold catalysts function similarly to palladium catalysts for the Sonogashira cross-coupling reactions.…”
mentioning
confidence: 97%
“…This lack of precedents for Au(III)-diacetylides might indicate that the reactivity of the alkynes once s-bound to Au(III) is very high, including a potential reductive elimination. It has been proposed that the reductive elimination from a tetracoordinated planar Au(III) complex is favoured respect to other metals 33 since it leaves behind a two-coordinated Au(I) complex stabilized by relativistic effects [39][40][41] . To study the reductive elimination of alkynes from Au(III) and also if the distal size selectivity occurs at this stage, the Au(III) complex PPh 3 AuCl 3 was prepared 42 and the corresponding Au(III) acetylide complex of 1-dodecyne 1b was forced to be formed 43 .…”
Section: Resultsmentioning
confidence: 99%